Hasil Laut dan Kehidupan Nelayan Pulau Pura Kabupaten Alor Nusa Tenggara Timur - Mardianti Yosefina Maleiku; Mrs. Nurlela (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to determine: (1) How is the impact of marine products on the lives of fishermen on Pura Island. (2) How to use and preserve marine products on Pura Island. This study uses a type of qualitative research which is analyzed descriptively. Data collection techniques were obtained by field research through observation, interviews, and documentation methods involving 8 informants. The results of the field research show that: (1) Marine products and fishermen on Pura Island are two elements that cannot be separated, marine products have a very important role for fishermen's lives and only by utilizing marine products can the community (fishermen) survive, and be able to meet all the necessities of life. (2) In utilizing marine products as the main source of fishermen, fishermen who are on Pura Island strive to maintain and preserve marine products, every effort is made to preserve marine products so that they remain. If marine products as a source, especially for them, become extinct, the lives of fishermen will be threatened with no source of income.